7-2y-5=8

Add 5 to both sides of the equation.

7-2y=8+5

Add 8 and 5.

7-2y=13

7-2y=13

To remove the radical on the left side of the equation, square both sides of the equation.

7-2y2=132

Multiply the exponents in ((7-2y)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(7-2y)12⋅2=132

Cancel the common factor of 2.

Cancel the common factor.

(7-2y)12⋅2=132

Rewrite the expression.

(7-2y)1=132

(7-2y)1=132

(7-2y)1=132

Simplify.

7-2y=132

Raise 13 to the power of 2.

7-2y=169

7-2y=169

Move all terms not containing y to the right side of the equation.

Subtract 7 from both sides of the equation.

-2y=169-7

Subtract 7 from 169.

-2y=162

-2y=162

Divide each term by -2 and simplify.

Divide each term in -2y=162 by -2.

-2y-2=162-2

Cancel the common factor of -2.

Cancel the common factor.

-2y-2=162-2

Divide y by 1.

y=162-2

y=162-2

Divide 162 by -2.

y=-81

y=-81

y=-81

Solve for y square root of 7-2y-5=8